Pengembangan Model Pembelajaran Melalui Multimedia Macromedia Flash Pada Permainan Sepakbola Siswa Kelas VII SMPN 2 Sumbergempol Tulungagung - Hadi Winarto (Jurnal Simki Postgraduate, 2023)
This research is research and development by going through the preliminary stages, developing learning designs, production, and product evaluation. After the production stage, then the product validation stage by media experts and material experts. Data were obtained through questionnaires about the quality of learning multimedia products regarding aspects of appearance, content/material, learning, and qualitative data suggestions and input used as material for improvement. Qualitative data is data obtained from questionnaires in the form of statements and not the results of calculating numbers analyzed with descriptive statistics and quantitative data is data obtained from numbers from initial assessments starting from small group trials and large group trials where to find out the success of the product to be developed. From the results of the large group questionnaire, students can be said to be very good where the frequency of 13 is very good, namely 86.67 and the frequency of 2 presentations is good, namely 13.33 and the results of student comments that learning using Macromedia Flash multimedia on learning material for football games is very fun and easy to understand. . This research produced a Macromedia Flash-based learning multimedia product for soccer games that students can use as companion material for soccer games. As for the validation of material experts and media experts "very good", while the assessment on the test obtained: display aspect score 4.35 (very good), content aspect score 4.27 (very good), learning aspect score 4.30 (very good). The overall average in the student trial is 4.25 including the "good" criterion.